Impact of apigenin and seashell nano-additives on the antifungal and roughness behavior of a soft denture liner: Antifungal and roughness of apigenin and seashell modified soft liner - Jaffer, Nadia Tawfiq; Hasan, Rizgar Mohammed-Ameen; Taqa, Ghada Abd Alrhman (Cellular and Molecular Biology, 2023)
Fungal colonization of the soft denture liner is the first step in the development of denture-induced stomatitis. The study aims to assess apigenin and seashell nano-additives for their antifungal efficacy and their impact on the surface roughness of a soft denture liner. The study was accomplished in the Colleges of Dentistry in Duhok, Mosul and Hawler Medical Universities. The Antifungal efficacy against Candida albicans was performed by the minimum inhibition concentration (MIC), for apigenin the MIC was determined by agar well diffusion and set at (0.25%, 0.5% and 1%) while for seashells, MIC was determined by broth dilution and set at (1.25%, 2.5% and 5%). Fungal adhesion was conducted on seven groups (unmodified soft liner and six groups of the modified liner with the antifungal concentrations (three for each nanoparticle). A total of forty-nine square-shaped specimens (10*10*2mm) of (GC, Super-soft, heat-cured, USA) soft liner were prepared, the adherent fungal cells were enumerated under a light microscope for each specimen in four fields and the results were expressed as fungal cells/mm2. For the surface roughness, forty-nine specimens of (20*10*3 mm) of the soft liner were prepared and the average surface roughness was obtained in µm using a profilometer (Talysurf, Taylor Hobson, UK). Apigenin and seashell-modified soft liner observed a significant decrease in both fungal adhesion and surface roughness compared to the unmodified liner and the reduction was related directly to the concentration of both additives. Apigenin and seashell nano-additives were effective as antifungal agents beside improving the surface roughness of the soft liner.